Vocational High School Building Village Program as Link and Match for Community Economic Development - Purwaningsih, Siswanti; Yoto, Yoto (Teknologi dan Kejuruan: Jurnal Teknologi, Kejuruan, dan Pengajarannya, 2022)
The Ministry of Education and Culture created a synergy between VHS and the village administrators with the support of industry partners.The policy of link and matchis considered to be a strategy for exploring potencies and competencies demanded in the job market and social life.This research is intended to provide a handy reference for VHS and related parties engaged in the VHS Building Village. The kind was descriptive research with a case study design. The findings showed that this program was conducted on the basis of a collaboration of expertise program of  1 of Boyolangu, industry partners, and the administrator of Kepuh Village. This was carried out throught procedures: mapping potency and ecosystme services/integrated patterns, planning the program, fostering collaboration, developing implementation strategies and making performance measurement. The efforts to strenthen the role of VHS in improving village economy were made in the strategies involving education, entrepreneurship, innovation of appropriate technologies, and community empowerment. The performance measurement of the program was made by analyzing its effectiveness and influence on the economic condition before and after the conduction of the program, which can be seen form the program’sinputs, processes, outputs, outcomes and impacts